2022
DOI: 10.1371/journal.ppat.1010386
|View full text |Cite
|
Sign up to set email alerts
|

Early and mid-gestation Zika virus (ZIKV) infection in the olive baboon (Papio anubis) leads to fetal CNS pathology by term gestation

Abstract: Zika virus (ZIKV) infection in pregnancy can produce catastrophic teratogenic damage to the developing fetus including microcephaly and congenital Zika syndrome (CZS). We previously described fetal CNS pathology occurring by three weeks post-ZIKV inoculation in Olive baboons at mid-gestation, including neuroinflammation, loss of radial glia (RG), RG fibers, neuroprogenitor cells (NPCs) resulting in disrupted NPC migration. In the present study, we explored fetal brain pathologies at term gestation resulting fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Baboons have been successfully used as an in vivo NHP model for multiple human infectious diseases, including Bordetella pertussis, Zika virus, RSV and more recently SARS-CoV-2 [41,[76][77][78][79][80][81][82]. A recent study by Singh et al, [41] compared the responses of rhesus macaques, marmosets and baboons to acute infection with SARS-CoV-2 and demonstrated that baboons are susceptible to SARS-CoV-2 and develop more extensive pulmonary pathology associated with the human disease compared to rhesus macaques and marmosets.…”
Section: Discussionmentioning
confidence: 99%
“…Baboons have been successfully used as an in vivo NHP model for multiple human infectious diseases, including Bordetella pertussis, Zika virus, RSV and more recently SARS-CoV-2 [41,[76][77][78][79][80][81][82]. A recent study by Singh et al, [41] compared the responses of rhesus macaques, marmosets and baboons to acute infection with SARS-CoV-2 and demonstrated that baboons are susceptible to SARS-CoV-2 and develop more extensive pulmonary pathology associated with the human disease compared to rhesus macaques and marmosets.…”
Section: Discussionmentioning
confidence: 99%